Haemostatic Mechanism in the Uterine Circulation during Placental Separation. Issue 5709 (6th June 1970) - Bonnar, John; Prentice, C. R. M.; McNicol, G. P.; Douglas, A. S.
Abstract : The haemostatic mechanism in the uterus during parturition was investigated in 12 patients being delivered by caesarean section. Detailed sequential study of the blood coagulation and fibrinolytic systems in the uterine circulation showed that placental separation is accompanied by a striking local activation of the clotting mechanism. Uterine vein blood draining the placental site while the placenta was separating showed a pronounced shortening of the whole-blood clotting-time, a significant shortening of other clotting-tests, and a sharp increase in factor VIII activity, though these changes were transitory. After delivery the level of fibrinogen and circulating platelets steadily increased and factor VIII activity remained high. Activation of the clotting mechanism during placental separation appears to play an essential part in controlling uterine haemorrhage. The subsequent changes in the haemostatic mechanism in the puerperium are likely to predispose to thromboembolic complications.